A case of familial systemic sclerosis - Shreeja Jha; Mohammed Fahad Khan; Aditi Ravindra (Journal of Clinical and Scientific Research)
We present the case of a 27-year-old male who was examined and found to have bilateral sensory axonal neuropathy, proximal muscle weakness and limb abnormality. Antibodies against ribonucleic acid polymerase and anti-Scl-70 were found during his serological examination. According to our patient, his mother and his maternal grandfather both had the same symptoms. He was a second-degree consanguineous child of a married couple. Six of the nine siblings of the mother and nine of the 11 siblings of the grandfather expressed similar symptoms. Given the strong family history, full exome sequencing carried out using the next-generation sequencing method showed an interferon regulatory factor 5 (IRF5) IRF5 rs2004640 GT substitution. The case intends to draw attention to the genetic and familial basis of systemic sclerosis.